Chemical simulations of quantum systems using quantum computers - review of algorithms and their experimental verification - Wojciechowski, Konrad; Kurowski, Krzysztof; Mazurek, Cezary (Postępy biochemii, 2024)
Computer simulations using ever-increasing computing power and machine learning techniques allow advanced molecular modelling, molecular dynamics simulations and studies of intermolecular interactions. However, due to the complexity of biological systems and chemical processes at the molecular level, their accurate representation using classical computer models and techniques has faced a number of significant limitations for many years. A new and promising direction for the development of computational science and its potential applications in biochemistry is quantum computing and its integration with classical high-performance supercomputing systems. This article responds to the growing interest in the use of available quantum computers in exemplary applications. In this paper, we aim to provide an overview of the basic notions involved in the development of quantum algorithms and simulations related to issues at the interface of quantum chemistry and biochemistry. In addition, the article introduces the basic principles of performing simulations using the state-of-the-art quantum computers in the era of Noisy Intermediate-Scale Quantum (NISQ). Experimental results of the classical-quantum algorithm Variational Quantum Eigensolver (VQE) for example molecules H2 and CH+ are also presented. Despite the many shortcomings of currently available quantum computers, the analysed VQE algorithm proved to be effective in approximating the ground state of molecules using a minimal functional basis.